2014
DOI: 10.1111/ajps.12162
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fact‐Checking on Elites: A Field Experiment on U.S. State Legislators

Abstract: Does external monitoring improve democratic performance? Fact-checking has come to play an increasingly important role in political coverage in the United States, but research suggests it may be ineffective at reducing public misperceptions about controversial issues. However, fact-checking might instead help improve political discourse by increasing the reputational costs or risks of spreading misinformation for political elites. To evaluate this deterrent hypothesis, we conducted a field experiment in nine U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(131 citation statements)
references
References 54 publications
0
122
0
9
Order By: Relevance
“…For example, Butler and Nickerson () provide experimental evidence that when legislators learn about their constituents' policy preferences, they move their voting behavior toward these constituents' preferences to avoid an electoral backlash. Similarly, Nyhan and Reifler () find that the threat of “fact‐checking” induces legislators to avoid incorrect claims during the election period. Thus, incumbents have incentives to adjust their environmental and energy voting in accordance to voter preferences.…”
Section: The Partisan Politics Of Environmental Voting In the Congressmentioning
confidence: 98%
“…For example, Butler and Nickerson () provide experimental evidence that when legislators learn about their constituents' policy preferences, they move their voting behavior toward these constituents' preferences to avoid an electoral backlash. Similarly, Nyhan and Reifler () find that the threat of “fact‐checking” induces legislators to avoid incorrect claims during the election period. Thus, incumbents have incentives to adjust their environmental and energy voting in accordance to voter preferences.…”
Section: The Partisan Politics Of Environmental Voting In the Congressmentioning
confidence: 98%
“…Facebook should continue to strive towards providing users with more contextual information about news stories. Research has shown that the effects of fact-checking can be complex, and some have even argued that it can be counter-productive (Nyhan and Reifler, 2015;Lazer et al, 2018). But an important piece of research has suggested that Facebook's recent fact-checking efforts have had success in reducing the amount of misinformation in the average user's feed (Allcott, Gentzkow, and Yu, 2018).…”
Section: Expand Context and Fact-checking Facilitiesmentioning
confidence: 99%
“…(Rare examples of studies on preventing misinformation are [34,35].) The other reason is that the correction of misinformation is largely cognitive and thus conducive to simple laboratory experiments, whereas the prevention of misinformation is largely sociological and thus requires a more complex and case-specific analysis.…”
Section: Preventing Superintelligence Misinformationmentioning
confidence: 99%